Frontispiece: Photoredox Organic Synthesis Employing Heterogeneous Photocatalysts with Emphasis on Halide Perovskite. Issue 58 (15th October 2020) - Lin, Yixiong; Guo, Jun; San Martin, Jovan; Han, Chuang; Martinez, Ramon; Yan, Yong
Abstract : Heterogeneous photocatalysts employed in the field of visible light induced complex photoredox organic synthesis is reviewed by Yong Yan et al. on page 13118 ff., with specific emphasis on halide perovskite based photoredox chemistry. They introduce the important photochemical and photophysical properties that govern a photoredox process. The latest progress regarding heterogeneous photocatalysis especially the perovskite based photocatalytic organic synthesis are summarized. They rationalize the great potential of halide perovskite for being the possible replacement of current noble metal based photocatalysts in terms of photophysical properties, band tuning, price, substrate activation, TON, etc., and its potential for being industrialized in future pharmaceutical synthesis application. They also discuss the current existing issue of perovskite photocatalysts and provide some perspectives of future research directions.